Integrating proteomics into precision oncology - Wahjudi, Leonie; Bernhardt, Stephan; Abnaof, Khalid; Horak, Peter; Kreutzfeldt, Simon; Heining, Christoph; Borgoni, Simone; Becki, Corinna; Berg, Daniela; Richter, Daniela; Hutter, Barbara; Uhrig, Sebastian; et al. (International journal of cancer, 2021)
DNA sequencing and RNA sequencing are increasingly applied in precision oncology, where molecular tumor boards evaluate the actionability of genetic events in individual tumors to guide targeted treatment. To work toward an additional level of patient characterization, we assessed the abundance and activity of 27 proteins in 134 patients whose tumors had previously undergone whole-exome and RNA sequencing within the Molecularly Aided Stratification for Tumor Eradication Research (MASTER) program of National Center for Tumor Diseases, Heidelberg. Proteomic and phosphoproteomic targets were selected to reflect the most relevant therapeutic baskets in MASTER. Among six different therapeutic baskets, the proteomic data supported treatment recommendations that were based on DNA and RNA analyses in 10% to 57% and frequently suggested alternative treatment options. In several cases, protein activities explained the patients' clinical course and provided potential explanations for treatment failure. Our study indicates that the integrative analysis of DNA, RNA and protein data may refine therapeutic stratification of individual patients and, thus, holds potential to increase the success rate of precision cancer therapy. Prospective validation studies are needed to advance the integration of proteomic analysis into precision oncology.
First published: 19 September 2020
Gesehen am 02.10.2020